Measures to build material environment for children aged 5-6 to discover science at kindergarten schools in Lap Vo district, Dong Thap province - Tran, Nguyen Thi Nhu Mai; Dao, Thi Bao Tran; Cao, Huyen Hao; Nguyen, Thuy Diem (Tạp chí Khoa học Đại học Đồng Tháp, 2023)
Building a physical environment for children to explore science is an extremely important task in the process for preschool education goal, towards developing their cognitive capacity by experiencing the surrounding environment in various forms. This also helps to meet their needs and interests under the motto "learning by playing, playing through learning", promoting all potentials and personalities. The article mentions the concepts of the physical environment, the principles of building a physical environment for children aged 5-6 to explore science and points out the difficulties in this task. The article also proposes measures to build the target environment, such as: promoting real local conditions; closely coordinating with young families; choosing toys based on children's interests and promoting children's ability to make toys. These measures will contribute to improving the effectiveness of the design of the physical environment for children in scientific discovery activities.